Forging Historical Truth: Samples from Early Modern and Modern Italian Art Literature - Perini Folesani, Giovanna (Actual Problems of Theory and History of Art, 2024)
Drawing mostly on a number of factual and methodological contributions I have published over the years on the fabrication of visual and verbal documents in art history and/or on their interpretative manipulation, I provide a brief survey of case studies where documented facts clash against received but unsubstantiated wisdom. The sampling will be centered on Bolognese art and art literature from the 16th through to the 18th centuries. It will include the questioning of the assumed and yet unproven close relations between Cardinal Gabriele Paleotti’s pastoral and theological attitude and the Carracci reform of painting, i.e. the latter’s supposed allegiance to Counterreformation values; the actual impact and degree of pervasiveness of Counterreformation (with its nuanced, local interpretations) in different cultural contexts, like private literary academies (e.g. the Bolognese Accademia dei Gelati) or the production of new, uncodified and therefore unacceptable Old Testament iconographies in Bologna and elsewhere in Italy and Europe, from Germany, Switzerland, France and England to Poland and even Russia; the conflicting interpretations of the Carracci’s work produced by Bellori and Malvasia, and the political and cultural reasons why the former’s lies and inaccuracies have got and still get the upper hand in scholarly studies over the latter’s truth and accuracy; finally how Luigi Crespi, a notorious con-man, made his official debut in art literature in 1757 by systematically debunking Bellori’s last work, Descrizione delle immagini dipinte da Raffaelle d’Urbino (published posthumously in 1695). The last example stands to prove that “ it takes a thief to catch a thief”, and also how ineffectual telling the truth can be, when intellectual conformism, stubborn ignorance and oversemplification turn into the most effective allies of masterminded manipulation, helping lies to prevail and create consensus. Debunking is always swimming against the tide, ever since Lorenzo Valla wrote De falso credita et ementita Constantini donatione (1440), whose impact on art history writing is witnessed by Lorenzo Ghiberti’s II Commentary.
Keywords: forgery; debunking; Luigi Crespi; Lorenzo Ghiberti; Lorenzo Valla; Carlo Cesare Malvasia; Giovan Pietro Bellori; Ludovico Carracci; Giovannino da Capugnano; Giovanni Andrea Gilio